Illuminating a neglected population: epidemiological and clinical features of silicosis and tuberculosis among former gold miners from Lesotho - Maboso, Botembetume (Department of Public Health and Family Medicine, 2024)
Background Silicosis, tuberculosis (TB), and human immunodeficiency virus (HIV) infection, singularly and together, are all global health concerns. Southern Africa, with its high HIV and TB prevalence and incidence, is the most affected region by these conditions. The large South African mining industry, especially gold mining, is known as the amplifier of this triple epidemic of silicosis, TB and HIV. Furthermore, ex-mineworkers from South African mines have a higher mortality rate than active mineworkers and the general population. They carry a heavy burden of silicosis, TB, HIV and other pulmonary diseases, which strongly contribute to this higher mortality. Lesotho is a tiny country with about 2.3 million inhabitants of which about 95,000 are exgold miners from South African industry. Over 40% of Basotho ex-gold miners attending invited examinations have silicosis, more than 50% of them have been treated at least once for TB, and 60% have lung lesions on chest x-ray (CXR) suggestive of TB. In this country, many silicosis cases have been treated repeatedly for TB, and some have been documented as MDR-TB on the basis of plain CXR alone, even when bacteriologic tests gave negative results. Objectives To address the problem of TB, in general and the high morbidity and mortality among exgold miners, in particular, we designed three separate studies with the following objectives: (1) To illustrate the challenges in diagnosing active TB in this setting, specifically in distinguishing pulmonary TB (past and current) from silicosis; (2) to assess the performance of the screening CXR and symptoms of cough and fever in the diagnosis of active TB disease using Xpert MTB/RIF sputum test as the reference standard; and (3) to identify predictors of silicosis, tuberculosis, and associated hypoxaemia to better understand the predictive effects of comorbidity, the determinants of severity, and health care implications. Methods Three separate but inter-related sub-studies (two cross-sectional and one case series) were conducted from a single database of men who worked in South Africa gold mines for at least 12 months and visited Mafeteng Occupational Health Service Centre from January 2017 to November 2018. We analysed the medical history information, CXR, and Xpert MTB/RIF sputum test results for all attendees. For sub-study 1, four cases were discussed. For sub-study 2, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV), of CXR and symptoms, in the diagnosis of TB, were computed. For sub-study 3, multiple logistic regression modelling of various variables against silicosis, active TB and hypoxaemia as dependent variables in separate models was carried out. Findings The first study of four cases demonstrated that ex-gold miners from the South African mines present with complex lung disease, with poor agreement between radiological findings and clinical presentations, poor agreement between radiographs suggestive of TB and Xpert MTB/RIF sputum results, and overlap of clinical and radiological presentations of silicosis and TB. The second study composed of 2572 ex-gold miners and revealed CXR sensitivity, specificity, positive predictive value (PPV) and negative predictive values (NPVs) of 0.93 (95% CI: 0.87-0.99), 0.41 (95% CI:0.39-0.99), 0.05 (95% CI:0.04-0.06), and 0.99 (95% CI:0.98-1), respectively. Symptoms, on their own, could only identify about half of the active TB cases (i.e., a sensitivity of 0.45, 95% CI:0.34-0.56). Computing of either an abnormal CXR or symptoms of cough or fever slightly increased the sensitivity (0.96, 95% CI: 0.92-1) while it substantially decreased specificity (0.33, 95% CI: 0.31-0.35). The third study composed of 2678 ex-gold miners and found high odds of silicosis among ex-gold miners who had longer lengths of service (OR: 2.21, 95% CI: 1.68-2.74), higher level of dust exposure (OR: 1.57, 95% CI: 1.28-1.86), a history of past TB (OR: 2.66, 95% CI: 2.21-3.11), shortness of breath (OR: 1.47, 95% CI: 1.14-1.80), and decreased lung function. HIV-infected ex-gold miners had significantly lower odds of silicosis than their colleagues who were HIV-negative (OR: 0.62, 95% CI: 0.50-0.73). There were high odds of active TB among ex-gold miners who had silicosis (OR: 2.30, 95% CI: 1.56-3.08) and those who were HIV-positive (OR: 1.57, 95% CI: 1.04-2.10). Furthermore, there were high odds of hypoxaemia among those with a history of past-TB (OR: 1.48, 95% CI: 1.17- 1.79) and those with silicosis (OR: 2.41, 95% CI: 1.92-2.90), while the odds of hypoxaemia were significantly lower among HIV-infected ex-gold miners. Conclusions These studies demonstrate that mining work, and prominently exposure to silica dust, continue to cause morbidity in ex-gold miners, years after exposure has ceased, imposing a health cost on the poor ex-miner and the health system of their countries. They highlight the permanency of the situation caused by silica exposure; reveal the gap in the compensation system, either through the government (i.e., ODMWA, CCOD) or nongovernment channels (i.e., Tshiamiso Trust, Q(h)ubeka Trust), by demonstrating that silicainduced and aggravated conditions impose persistent/lifelong health costs to ex-gold miners that exceed current compensation. Consequently, they highlight the needs for the compensation system and law enforcement agencies to consider providing for and extending support for mining-induced medical needs (i.e., long-term management of chronic lung diseases, ambulatory or long-term oxygen therapy) to ex-gold miners, including those outside of South Africa borders. There is a need for training of healthcare providers in the labour sending communities in the diagnosis and management of mining-induced medical problems (silicosis, TB, silicotuberculosis, COPD, etc.). Clinicians and policy makers need to consider adjusting the new TB management policy to the predictive values of symptoms and the CXR in diagnosing active TB in this population. In addition to action to provide access to diagnosis, care and compensation, we need further research into the combined lung disease burden, and special health service and social security needs of this long neglected population.